Pertimbangan Hakim Menetapkan Asal Muasal Hibah Wasiat Terhadap Salah Satu Ahli Waris Adat Batak Toba - Ambarita, Mylanta; Ninik Darmini (Notaire, 2025)
This study examines an inheritance dispute among siblings in the Toba Batak indigenous community who have long settled in Jakarta (new local). The case proceeded through all judicial levels in Indonesia, from the District Court to the Judicial Review. The research analyzes judges’ legal considerations in determining the origin and validity of a testamentary gift granted to one heir, viewed from the perspectives of the Civil Code and Toba Batak customary law. Employing a descriptive normative legal method, this study relies mainly on secondary legal materials, supported by interviews with civil judges, and analyzed qualitatively. The findings reveal divergent judicial interpretations. The District and High Courts emphasized formal aspects by validating Deed of Gift of Will No. 3/2005 as an authentic notarial deed. In contrast, the Supreme Court and Judicial Review prioritized material aspects, upholding substantive justice and protecting heirs’ legitime portie. Consequently, the testator’s freedom is limited to ensure fairness and the protection of heirs’ rights. The Judicial Review, which annulled eleven such deeds, affirms that the validity of testamentary gifts must be assessed both formally and substantively, consistent with the Civil Code and Toba Batak customary law principles.